Instagram Sebagai Sarana Promosi Wisata di Kabupaten Jember Pada Akun Instagram @pesonajember - Ahmad Fauzi; Siti Sholihatul Mahmudah; Choirul Bachtiar (Jurnal Ilmu Komunikasi PROGRESSIO, 2022)
Technology and information is currently growing rapidly so that it can be used by anyone with creative work and to communicate without any limitations. Along with the development of the times, there is a new media with the type of social media Instagram. Instagram is in great demand by many people, so it is easier to convey any information in the form of writing, photos or videos. The purpose of this study is to find out how account managers can attract other Instagram users to participate in promoting tourism in Jember Regency and how to respond to tourist uploads on the @pesonajember Instagram account. This research method uses descriptive qualitative research methods through observation, interviews, documentation and literature study. The results of this study are Instagram can be used to convey information in the form of promoting tourism in Jember Regency. The communication process is appropriate in the mass communication process and there are several effects that are caused to other Instagram users who see travel posts. The existence of the @pesonajember account makes some tours more known by many people.